Review of Article 34 Paragraph (1) of the 1945 Constitution concerning Handling Abandoned Children (Case Study of the Labuhanbatu Regency Social Service) - Fatwa Sari; Toni Toni (Budapest International Research and Critics University, 2022)
Whereas abandoned children are children whose parents are unable to take responsibility and are unable to meet their basic needs due to economic factors, and the family is not harmonious. This type of research uses Juridical Empirical Research. While empirical juridical is a legal research method that looks at the law directly in looking at direct social facts that distinguish facts from norm values. Research Objects Labuhanbatu Social Service The research results if viewed from the Act Article 34 paragraph (1) that